The Role of Correspondence or Letter in the World of Business - Kholil, Lu'lu' Najmi (Pascasarjana Universitas Pasundan, 2024)
Correspondence is a very important communication tool and is carried out at all times in daily tasks. Generally, correspondence consists of letters and memoranda. In the business world, correspondence is needed because business correspondence is an activity of correspondence between one party and another party, both individuals and institutions, which is related to business matters and definitely requires a good means of communication between internal companies and external parties. The correspondence function itself involves the work of dictation, typing and conveying information.